2011
DOI: 10.1016/j.jvs.2010.07.055
|View full text |Cite
|
Sign up to set email alerts
|

Inference from clinical and fluid dynamic studies about underlying cause of spontaneous isolated superior mesenteric artery dissection

Abstract: Development of SISMAD seems to be less likely the result of hypertension or connective tissue disease but more likely due to hemodynamic force caused by convex curvature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
71
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 92 publications
(75 citation statements)
references
References 24 publications
4
71
0
Order By: Relevance
“…9, 11 Others have stated that the shear stress at the maximum curve of the SMA was the cause of the dissection, based on a hemodynamic simulation study. 19,20 However, our study indicated that the dissection origin was located more proximal to the pancreatic edge or the maximum curve of the SMA, and less than half of patients showed conditions similar to those described by Solis et al 9 and Park et al 19 Thus, the mechanism of spontaneous isolated SMA dissection remains unknown, but may include multiple etiologies. Concerning treatment of spontaneous isolated SMA dissection, a relatively high proportion of patients requiring surgical intervention has been previously reported.…”
Section: Disclosuressupporting
confidence: 51%
“…9, 11 Others have stated that the shear stress at the maximum curve of the SMA was the cause of the dissection, based on a hemodynamic simulation study. 19,20 However, our study indicated that the dissection origin was located more proximal to the pancreatic edge or the maximum curve of the SMA, and less than half of patients showed conditions similar to those described by Solis et al 9 and Park et al 19 Thus, the mechanism of spontaneous isolated SMA dissection remains unknown, but may include multiple etiologies. Concerning treatment of spontaneous isolated SMA dissection, a relatively high proportion of patients requiring surgical intervention has been previously reported.…”
Section: Disclosuressupporting
confidence: 51%
“…4 When asymptomatic SISMAD was detected incidentally, patients were observed on an outpatient basis annually. Indications for intervention, either endovascular or surgical, included persistent abdominal pain not relieved by conservative treatment lasting 7 days or longer, or signs and symptoms suggestive of bowel ischemia.…”
Section: Methodsmentioning
confidence: 99%
“…We previously reported our observation regarding correlation between types of SISMAD on CT angiogram (CTA) and clinical features and relation between wall shear stress at the SMA and anatomic features of SMA. 3,4 To our knowledge, this is the largest series of clinical follow-up of SISMAD patients from a single institution. In the present study, we attempted to determine the natural history of SISMAD.…”
mentioning
confidence: 99%
“…The presence of uncontrolled hypertension, observed in about 30% of the cases, may be an additional risk factor for the occurrence of this condition 4 . Hemodynamic abnormalities caused by the curvature at the origin of the SMA could be another etiologic possibility, according to Park et al 5 . The natural history of the disease is unclear and varies among cases.…”
Section: Discussionmentioning
confidence: 99%
“…This recommendation is reinforced by experience in the treatment of spontaneous dissection of the carotid artery, where anticoagulation is effective in preventing thrombus formation 2,3 . Other authors, 4,5 however, claim that anticoagulation can help prevent thrombosis and obliteration of the false lumen, but may increase the possibility of SMA rupture.…”
Section: 8mentioning
confidence: 99%